Gliomas de alto grado en adultos - Sinning O., Mariana (Revista Hospital Clínico Universidad de Chile, 2009)
Malignant gliomas represent 80% of primary malignant central nervous system tumors. It generally presents with headache, epilepsy, cognitive change, dysphasia, or progressive hemiparesia. Current standard treatment for malignant glioma includes: surgical resection or biopsy, radiation therapy and/or chemotherapy. The prognosis of malignant gliomas is still dismal despite aggressive treatment attempts. Understanding the molecular pathogenesis of glioma may lead to a rational development of new therapies. This review summarizes the diagnosis and management of these tumors in adults.